2020
DOI: 10.32674/jis.v10is3.3202
|View full text |Cite
|
Sign up to set email alerts
|

The Emotional Experiences of Indonesian PhD Students Studying in Australia during the COVID-19 Pandemic

Abstract: This narrative study aims to explore the emotional experiences of two Indonesian students pursuing a doctorate (PhD) degree in Australia during the COVID-19 pandemic. Drawing on semi-structured interview data, we found that the prevalence of COVID-19 affected the participants’ emotions and behaviors. Both participants experienced different emotions and behaviors in facing various challenges during the pandemic. The study stresses the importance of independence, family support, social support, and university su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
1
4
0
1
Order By: Relevance
“…To keep up the motivation of the students, the school already determined the funds for the students such as data packages to support the online instructional activities. In line with several previous studies, this finding revealed that the support from school indeed helped the students to maintain their online learning (Supiani et al, 2020;Taloko & Putra, 2020). Besides, the family and peers also helped the students in fulfilling the technological needs.…”
Section: Students' Strategies To Overcome Emotional Challengessupporting
confidence: 90%
See 2 more Smart Citations
“…To keep up the motivation of the students, the school already determined the funds for the students such as data packages to support the online instructional activities. In line with several previous studies, this finding revealed that the support from school indeed helped the students to maintain their online learning (Supiani et al, 2020;Taloko & Putra, 2020). Besides, the family and peers also helped the students in fulfilling the technological needs.…”
Section: Students' Strategies To Overcome Emotional Challengessupporting
confidence: 90%
“…Furthermore, the students also admitted that they could overcome difficulties in understanding the material by asking peers and the teacher. This finding affirmed that negative feelings during the online learning process could be managed with the influence of the family, school, teacher and peers' supports (Nurfaidah et al, 2020;Puspitasari & Rahayu, 2020;Supiani et al, 2020).…”
Section: Students' Strategies To Overcome Emotional Challengesmentioning
confidence: 58%
See 1 more Smart Citation
“…Pokhrel and Chhetri (2021) who conducted a literature review on the impact of COVID-19 on students' teaching and learning found out that learners with a fixed mindset struggled to adjust, whereas learners with a growth mindset could quickly adapt to a new learning mode. Supiani et al (2020) investigated how two international students adapt their learning strategies during the pandemic.…”
Section: Students' Language Learning Strategies During the Covid-19 P...mentioning
confidence: 99%
“…Students develop their learning autonomy because they need to use different online tools to support their learning (Sepulveda-Escobar and Morrison, 2020). A study conducted by Supiani et al (2020) found that students have to become more independent to achieve their learning goals during the pandemic successfully. Since they become more autonomous, they also need to find their learning strategy.…”
Section: Introductionmentioning
confidence: 99%